Secluded and restrained patients' perceptions of their treatment. (25th September 2012) - Soininen, Päivi; Välimäki, Maritta; Noda, Toshie; Puukka, Pauli; Korkeila, Jyrki; Joffe, Grigori; Putkonen, Hanna
Abstract Though some empirical and anecdotal accounts can be located in the extant literature, it remains the case that little is known about how secluded/restrained (S/R) patients perceive their overall treatment. The purpose of this study was to explore patients' perceptions of their hospital treatment measured after S/R. The data were collected with a Secluded and Restrained Patients' Perceptions of their Treatment (S/R‐PPT) questionnaire from S/R patients aged 18–65 years. Ninety completed questionnaires were analysed. Patients perceived that they received enough attention from staff, and they were able to voice their opinions, but their opinions were not taken into account. Patients denied the necessity and beneficence of S/R. Women and older patients were more critical than men and younger patients regarding the use of restrictions. There were also statistically‐significant differences in responses among patients at different hospitals. It is concluded that patients' opinions need more attention in treatment decisions. To achieve this, psychiatric treatment needs genuine dialogue between patients and staff, and individual care should have alternatives and no routine decisions. Therefore, the treatment culture must improve towards involving patients in treatment planning, and giving them a say when S/R is considered.